Model Pembelajaran TGT sebagai Solusi untuk Meningkatkan Hasil Belajar Siswa SD pada Mata Pelajaran IPS - Rini Endah Sugiharti; Arrahim Arrahim; Meilina Herlita (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
Social Sciences (IPS) is a science designed to instill knowledge of values, attitudes, and understanding in subject matter so that students can participate in daily life. This study aims to improve student learning outcomes in elementary school social studies subjects. This type of research uses a qualitative approach and the data analysis process emphasizes the conclusion and comparison of literature reviews from several scientific journals that serve as guidelines. The results of this study illustrate that applying the Team Games Tournament (TGT) model will improve student learning outcomes in the cognitive domain of students which include C1 (Knowledge), C2 (Comprehension), C3 (Application), C4 (Analysis), C5 (Synthesis), and C6. (Evaluation) in social studies subjects. In addition, the Team Games Tournament (TGT) model can involve all students to develop active and creative learning activities and can foster a sense of duty and group work towards one another. Thus it can be concluded that the Team Games Tournament (TGT) model can be applied as a solution to improve student learning outcomes in elementary school social studies lessons.